2022
DOI: 10.1111/1365-2656.13678
|View full text |Cite
|
Sign up to set email alerts
|

Parasite dynamics in North American monarchs predicted by host density and seasonal migratory culling

Abstract: Insect–pathogen dynamics can show seasonal and inter‐annual variations that covary with fluctuations in insect abundance and climate. Long‐term analyses are especially needed to track parasite dynamics in migratory insects, in part because their vast habitat ranges and high mobility might dampen local effects of density and climate on infection prevalence. Monarch butterflies Danaus plexippus are commonly infected with the protozoan Ophryocystis elektroscirrha (OE). Because this parasite lowers monarch surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Contrasting evidence of no change in the number of tagged monarchs returning to Mexico in the fall suggested otherwise (Taylor et al, 2020), but that finding remains contested due to difficulties in accounting for changing tagging effort through time (Fordyce et al, 2020). In support of our assessment, a recent study of the monarch parasite, Ophryocystis elektroscirrha , has shown that nation‐wide prevalence has increased in the last 15 years, and that this increase is leading to considerable migratory losses and corresponding reductions in winter colony sizes (Majewska et al, 2021). Therefore, conservation attention along the migration routes, and/or actions that reduce parasite transmission, may be more imperative for the monarch's long‐term survival compared to efforts directed at the breeding grounds.…”
Section: Discussionsupporting
confidence: 76%
“…Contrasting evidence of no change in the number of tagged monarchs returning to Mexico in the fall suggested otherwise (Taylor et al, 2020), but that finding remains contested due to difficulties in accounting for changing tagging effort through time (Fordyce et al, 2020). In support of our assessment, a recent study of the monarch parasite, Ophryocystis elektroscirrha , has shown that nation‐wide prevalence has increased in the last 15 years, and that this increase is leading to considerable migratory losses and corresponding reductions in winter colony sizes (Majewska et al, 2021). Therefore, conservation attention along the migration routes, and/or actions that reduce parasite transmission, may be more imperative for the monarch's long‐term survival compared to efforts directed at the breeding grounds.…”
Section: Discussionsupporting
confidence: 76%
“…Our study suggests that nighttime warming and heatwaves that exceed the thermal limits of OE could shift the location of transmission hotspots and the seasonal timing of infection. OE prevalence has increased threefold over the past two decades [ 80 ], in part owing to warmer winters supporting resident monarch populations along the Gulf Coast, which typically have high prevalence owing to year-round breeding [ 79 ]. However, recent record-breaking high temperatures indicate that continued warming in the southeast USA could lead to reductions in summer infection prevalence through decreased host and parasite survival, as well as through indirect temperature effects like reduced availability and increased toxicity of milkweeds [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, prevalence of the monarch parasite Ophryocystis elektroscirrha ("OE") has increased ca. 10-fold in North America since the early 2000s (26). Parasite infection reduces monarch wing strength and flight capacity, contributing to migratory dropout (27,28).…”
Section: Discussionmentioning
confidence: 99%